Kudoa stigmatias sp. nov. (Cnidaria: Multivalvulida) infecting the brain of the marine fish Chaeturichthys stigmatias (Gobiiformes: Gobiidae) in the Yellow Sea, China - Dong, Jilei; Jiang, Yanhua; Tan, Zhijun; Yao, Lin; Liu, Pengxiang; Zhao, Xiaojing; Zhang, Jinyong (Zootaxa, 2026)
In this study, 20 specimens of Chaeturichthys stigmatias were collected from a fishing dock in Qingdao city, Shandong Province, China, and examined for parasitic infections. Kudoa spores were detected in the brains of 35% of the specimens. The mature spores were quadrate and hemispherical in lateral view, measuring 8.1±0.4 (7.1–8.8) μm in length, 13.5±0.4 (12.1–13.8) μm in width, and 11.8±0.4 (10.6–12.5) μm in thickness (n = 50). Each spore possessed four shell valves and four pyriform polar capsules measuring 4.0±0.2 (3.5–4.2) × 3.1±0.2 (2.7–3.5) μm. Morphological comparisons revealed distinct differences from previously described Kudoa species. Sequence analysis of the partial LSU rDNA further confirmed that this species did not match any known Kudoa species. Furthermore, the phylogenetic tree showed that it clusters with muscle-infecting Kudoa species but is distantly related to brain-infecting taxa. Based on morphological and molecular evidence, we describe Kudoa stigmatias sp. nov. as a novel species, representing the first documented case of myxosporean infection in Chaeturichthys species.